Oxidative Stress and Photodynamic Therapy of Skin Cancers: Mechanisms, Challenges and Promising Developments - Alessandro Allegra; Giovanni Pioggia; Alessandro Tonacci; Caterina Musolino; Sebastiano Gangemi (MDPI AG, 2020)
Ultraviolet radiation is one of the most pervasive environmental interactions with humans. Chronic ultraviolet irradiation increases the danger of skin carcinogenesis. Probably, oxidative stress is the most important mechanism by which ultraviolet radiation implements its damaging effects on normal cells. However, notwithstanding the data referring to the negative effects exerted by light radiation and oxidative stress on carcinogenesis, both factors are used in the treatment of skin cancer. Photodynamic therapy (PDT) consists of the administration of a photosensitiser, which undergoes excitation after suitable irradiation emitted from a light source and generates reactive oxygen species. Oxidative stress causes a condition in which cellular components, including DNA, proteins, and lipids, are oxidised and injured. Antitumor effects result from the combination of direct tumour cell photodamage, the destruction of tumour vasculature and the activation of an immune response. In this review, we report the data present in literature dealing with the main signalling molecular pathways modified by oxidative stress after photodynamic therapy to target skin cancer cells. Moreover, we describe the progress made in the design of anti-skin cancer photosensitisers, and the new possibilities of increasing the efficacy of PDT via the use of molecules capable of developing a synergistic antineoplastic action.